2019
DOI: 10.14202/vetworld.2019.605-608
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and phylogenetic tree of infectious laryngotracheitis virus in layers in Al-Diwaniyah province, Iraq

Abstract: Background and Aim: Infectious laryngotracheitis (ILT) of chickens is a substantial issue to be studied in Iraq because this disease is one of the most highly contagious respiratory diseases in the world caused by a herpesvirus. However, in Iraq, the ILT virus (ILTV) infection and disease have yet not been confirmed in layers, so farm owners do not vaccinate these layers. The current study aimed to document the detection and characterization of ILTV in layer hens from Al-Diwaniyah city, for the first time in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…Countries including USA, Canada, Brazil, Europe, Australia, China, Egypt, South Asia, Lebanon and Saudi Arabia have notified ILT outbreaks (Gowthaman et al 2020). Lastly, the disease have been reported in Iraq (Alaraji et al 2019) and Namibia (Molini et al 2019). In Turkey, the frequency of the disease that determined in present study is lower than other countries.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Countries including USA, Canada, Brazil, Europe, Australia, China, Egypt, South Asia, Lebanon and Saudi Arabia have notified ILT outbreaks (Gowthaman et al 2020). Lastly, the disease have been reported in Iraq (Alaraji et al 2019) and Namibia (Molini et al 2019). In Turkey, the frequency of the disease that determined in present study is lower than other countries.…”
Section: Discussioncontrasting
confidence: 47%
“…The positivity rates of backyards were quite lower than Aras et al (2018) and this difference may be related with the sensitivity of ELISA tests. Virus isolation and serological tests (fluorescent antibody technique, enzyme-linked immunosorbent assay, serum neutralization, and agar gel immunodiffusion) have been used for diagnoses but, these methods are laborious, time consuming and the sensitivities of serological tests are lower than PCR (Alaraji et al 2019). ILT continue to keep its importance throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…During the period of 2000-2013, the disease had been reported at least in 100 countries (Menendez et al 2014). Recently, ILTV was confirmed by molecular techniques in Al-Diwaniyah province, Iraq which was the first report from the country (Alaraji et al 2019). In 2018, three outbreaks of ILT were reported in Windhoek, Namibia causing huge mortality in commercial layers and broilers (Molini et al 2019).…”
Section: Epidemiologymentioning
confidence: 99%
“…The disease has been reported from several Asian (China, Georgia, India, Japan, Lebanon, Myanmar, Philippines, Sabah, Sarawak, Taiwan, Iraq and Uzbekistan), African (Cameroon, Uganda, Namibia, Egypt, Nigeria), North American (Canada, Delaware, Georgia, Mexico, Maryland, New Brunswick, North Carolina, Ontario, Pennsylvania and Virginia), Central American and Caribbean (Costa Rica, Trinidad and Tobago), South American (Argentina, Brazil, Chile, Peru, Suriname and Uruguay), European (Austria, Belgium, Denmark, Germany, Italy, Moldova, Norway, the Netherlands, Poland, Sweden, Switzerland and UK) and Oceania countries (Australia, Cook Islands, French Polynesia, Guam, Kiribati and New Zealand (Hidalgo 2003;Chac on and Ferreira 2009;OIE 2014;Magouz et al 2018;Alaraji et al 2019;Molini et al 2019). Very recently, it was reported that recombinant ILT virus and CEO vaccine-like virus are causing outbreaks in Eygpt (Bayoumi et al 2020).…”
Section: Epidemiologymentioning
confidence: 99%
“…A vaccination program immunizing against ILTV has not officially been adopted by the federal government of Iraq [15] because of the political and economical disturbances. However, some farmers import the live-attenuated vaccine illegally from neighboring countries such as Syria, Turkey, Iran, Saudi Arabia, and Jordan (Figure -1).…”
Section: Figure-7mentioning
confidence: 99%